2018
DOI: 10.22159/ajpcr.2018.v11i4.23965
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Various Virulence Properties of Drug-Resistant Klebsiella Isolates: An in Vitro Study Among “Superbugs”

Abstract: Objective: The objective of this study was to evaluate the various virulence factors among all extended-spectrum beta-lactamase (ESBL)-producing Klebsiella isolates.Methods: Klebsiella species (n=201) isolated from various non-repeated clinical samples from October 2016 to May 2017 were collected and identified by biochemical method and confirmed by BD Phoenix. Antibiotic susceptibility test was performed by Kirby-Bauer disc diffusion method, and ESBL detection was done by combined disc diffusion method. Capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The current study however is similar to the findings of Devrari and Pai [31] who reported a higher prevalence of Klebsiella species amongst older subjects within age groups of 41 -50, 51 -60 and 61 -70 years old; the study by Ndako et al [18] was also comparable with the present study as the authors recorded a higher prevalence amongst the older age group in their study. While the age distribution of Klebsiella infection in the current study may not be statistically significant (p > 0.05), it is important to note that Klebsiella infections occur in people of all ages; however, the highest risk groups appear to be the elderly, infants, and the immunocompromised [31], indicating that infection with the bacteria is associated with decreased immunocompetence; the observed prevalence of 28.1% among those aged 41 -50 years may also be due to hormonal changes that occur during menopause, which can increase the risk of UTIs in women. As oestrogen levels fall, vaginal and urethral tissues weaken and dry, rendering them more vulnerable to infection [32].…”
Section: Discussionsupporting
confidence: 92%
“…The current study however is similar to the findings of Devrari and Pai [31] who reported a higher prevalence of Klebsiella species amongst older subjects within age groups of 41 -50, 51 -60 and 61 -70 years old; the study by Ndako et al [18] was also comparable with the present study as the authors recorded a higher prevalence amongst the older age group in their study. While the age distribution of Klebsiella infection in the current study may not be statistically significant (p > 0.05), it is important to note that Klebsiella infections occur in people of all ages; however, the highest risk groups appear to be the elderly, infants, and the immunocompromised [31], indicating that infection with the bacteria is associated with decreased immunocompetence; the observed prevalence of 28.1% among those aged 41 -50 years may also be due to hormonal changes that occur during menopause, which can increase the risk of UTIs in women. As oestrogen levels fall, vaginal and urethral tissues weaken and dry, rendering them more vulnerable to infection [32].…”
Section: Discussionsupporting
confidence: 92%
“…Many recurrent infections are caused by biofilm-producing bacteria, which are difficult to eliminate. They manifests resistance to antibiotics by a variety of ways, including limited antibiotic penetration into biofilms and the expression of resistance genes (Devrari and Pai, 2018). All UPEC isolates were examined for their capability to produce a biofilm using two in vitro screening methods.…”
Section: Biofilm Formation In Upecmentioning
confidence: 99%